Aralin computerized cataloging system : database user guide - Fuerte, Virgilio C. (Makati, Metro Manila Fund for Assistance to Private Education, 1995)
ARALIN is an on-line bibliographic data base intended to computerize initially the Filipiniana collections and eventually the entire collection of libraries of participatory private colleges and universities in the country. It was activated by FAPE in response to the increasing demand for information services by educational administrators, faculty, graduate and undergaduate students, professionals, educational planners and general researchers. The manual is divided into two main sections: the overview of the ARALIN CCS and the user guide. The overview presents step-by-step procedures on the various functions related to data base maintenance and information retrieval using the ARALIN CCS, as well as relevant computer operator functions using MS-DOS. The manual also contains the CDS/ISIS menus and worksheets that are used to perform the various database functions in the ARALIN CCS.
Keywords: Cataloging -- Data Processing; Library catalogs -- Automation